Acusatiu preposicional i dislocació amb clític - Escandell Vidal, M. Victòria (Caplletra. Revista Internacional de Filologia, 2007)
Catalan is usually described as a language without prepositional accusative, with the only exception of some pronouns. The aim of this paper is to present some datashowing that in most spoken varieties prepositional accusatives are indeed licensed in a specific construction, namely when appearing as topics in Clitic-Dislocation.Interestingly enough, the preposition is systematically excluded with rhematic, nontopical, objects. Dialects differ with respect to the conditions governing the use of thepreposition with topics: whereas in written Catalan the preposition appears with pronouns only, spoken Central Catalan extends its use to proper names and humandefinites as well, and Ibizan shows the wider extension of the phenomenon, with prepositional marking for almost all kinds of topics (pronouns, proper names, human and non-human definites, and even inanimate indefinites). This shows that forCatalan the crucial factor for the occurrence of prepositional accusatives is topicality –not definiteness or animacy, as in Spanish.